Diluted Competition? Conflicts between Full- and Half-Siblings in Two Adult Generations - Tanskanen, Antti O.; Danielsbacka, Mirkka; Jokela, Markus; David-Barrett, Tamas; Rotkirch, Anna (Frontiers in Sociology, 2016)
Sibling relations are typically close but ambivalent, including both altruism and competition. Full siblings are often assumed to exhibit more altruism and less competition than half-siblings. However, previous empirical findings indicate that this assumption may not hold for sibling conflicts in contemporary humans. We study self-reported occurrence of sibling conflicts among adults in two generations with nationally representative data from the Generational Transmissions in Finland surveys in 2012. Respondents represent an older generation (born between 1945 and 1950, n = 2,015) and their adult children (born between 1962 and 1993, n = 1,565). Based on kin selection and parent-offspring conflict theory we expect reports of any conflict to be more likely between full siblings than half siblings, between maternal half siblings than paternal half-siblings, and among the younger generation compared to the older generation. Results mostly support our hypotheses. Full siblings were more likely to report conflicts than were maternal and paternal half siblings in the younger generation. In the older generation, full siblings were more likely to report conflicts with paternal but not maternal half siblings. The younger generation was also more conflict-prone than the older. Results held when controlling for contact frequency, emotional closeness, unequal parental treatment, and several socioeconomic variables, as well as for within-family effects. Thus, although full siblings are typically closer and have more contact in adulthood than half siblings do, they also appear to have more conflicts. We suggest that this can be explained by diluted resource competition over parental investment between half siblings in societies with serial monogamy.